OPTIMASI FORMULA TABLET HISAP EKSTRAK KULIT AKAR SENGGUGU (Clerodendrum serratum L. MOON) SEBAGAI SEDIAAN OBAT PENGENCER LENDIR (MUKOLITIK) DENGAN KOMBINASI BAHAN PENGISI MANNITOL-LAKTOSA-SUKROSA - Sulaiman, T.N. Saifullah; Puspita, Desi Elvira Cindy; Wahyono, Wahyono (Faculty of Pharmacy, Universitas Gadjah Mada, 2015)
Senggugu root bark (Clerodendrum serratum L. Moon) is known as a mucolitics. Senggugu root bark is made in the dosage form of lozenges in combination with sucrose, mannitol and lactose in order to obtain good flavor and comfortable when consumed. The purpose of this study was to determine the effect of the combination of fillers on the physical properties of granules and tablets as well as the composition of the combination of excipients to produce lozenges of extract of senggugu root bark with optimum physical properties. Seven formulas were made with a combination of mannitol, lactose and sucrose as follows: FI (100%: 0%: 0%), FII (0%: 100%: 0%), FIII (0%: 0%: 100%), FIV (50 %: 50%: 0%), FV (50%: 0%: 50%), FVI (0%: 50%: 50%), and FVII (33.3%: 33.3%: 33.3% ). The results showed that the combination of mannitol, lactose and sucrose affected the physical properties of the granules and lozenges of extract of senggugu root bark i.e. flow rate, hardness, dissolved time, compactibility and perceptive sense. The dominant amount of sucrose and lactose can improve the physical properties of granules and tablets. The optimal composition of the combination of mannitol, lactose and sucrose obtained from Design Expert 7.1.5. program was 5.491%: 37.387%: 57.122%, respectively.